Two-Dimensional Nanostructured Ti3C2Tx MXene for Ceramic Materials: Preparation and Applications - Xiao-Tong Jia; Hong-Wei Xing; Xing-Wang Cheng; Zhao-Hui Zhang; Qiang Wang; Jin-Zhao Zhou; Yang-Yu He; Wen-Jun Li (Nanomaterials)
Ti3C2Tx MXene, a novel two-dimensional transition metal carbide with nanoscale dimensions, has attracted significant attention due to its exceptional structural and performance characteristics. This review comprehensively examines various preparation methods for Ti3C2Tx MXene, including acid etching, acid–salt composite etching, alkali etching, and molten salt etching. It further discusses several strategies for interlayer exfoliation, highlighting the advantages and limitations of each method. The effects of these techniques on the nanostructure, surface functional groups, interlayer spacing, and overall performance of Ti3C2Tx MXene are evaluated. Additionally, this paper explores the diverse applications of Ti3C2Tx MXene in ceramic materials, particularly its role in enhancing mechanical properties, electrical and thermal conductivity, as well as oxidation and corrosion resistance. The primary objective of the review is to provide scientific insights and theoretical guidance for the preparation of Ti3C2Tx MXene and its further research and innovative applications in ceramic materials, advancing the development of high-performance, multifunctional ceramics.